Monitoring for antidepressant-associated adverse events in the treatment of patients with major depressive disorder: An international consensus statement. (4th July 2018) - Dodd, Seetal; Mitchell, Philip B.; Bauer, Michael; Yatham, Lakshmi; Young, Allan H.; Kennedy, Sidney H.; Williams, Lana; Suppes, Trisha; Lopez Jaramillo, Carlos; Trivedi, Madhukar H.; Fava, Maurizio; Rush, A. John; et al.
Abstract: Objectives: These recommendations were designed to ensure safety for patients with major depressive disorder (MDD) and to aid monitoring and management of adverse effects during treatment with approved antidepressant medications. The recommendations aim to inform prescribers about both the risks associated with these treatments and approaches for mitigating such risks. Methods: Expert contributors were sought internationally by contacting representatives of key stakeholder professional societies in the treatment of MDD (ASBDD, CANMAT, WFSBP and ISAD). The manuscript was drafted through iterative editing to ensure consensus. Results: Adequate risk assessment prior to commencing pharmacotherapy, and safety monitoring during pharmacotherapy are essential to mitigate adverse events, optimise the benefits of treatment, and detect and assess adverse events when they occur. Risk factors for pharmacotherapy vary with individual patient characteristics and medication regimens. Risk factors for each patient need to be carefully assessed prior to initiating pharmacotherapy, and appropriate individualised treatment choices need to be selected. Some antidepressants are associated with specific safety concerns which were addressed. Conclusions: Risks of adverse outcomes with antidepressant treatment can be managed through appropriate assessment and monitoring to improve the risk benefit ratio and improve clinical outcomes.